Preferences of patients with asthma or COPD for treatments in pulmonary rehabilitation - Kathrin Damm; Heidrun Lingner; Katharina Schmidt; Ines Aumann-Suslin; Heike Buhr-Schinner; Jochen van der Meyden; Konrad Schultz (Health Economics Review, 2021)
Introduction: Pulmonary rehabilitation (PR) aims to improve disease control in patients with chronic obstructive pulmonary disease (COPD) and asthma. However, the success of PR-programs depends on the patients' participation and willingness to cooperate. Taking the patients' preferences into consideration might improve both of these factors. Accordingly, our study aims to analyze patients' preferences regarding current rehabilitation approaches in order to deduce and discuss possibilities to further optimize pulmonary rehabilitation. Methods and analysis: At the end of a 3 weeks in-house PR, patients' preferences concerning the proposed therapies were assessed during two different time slots (summer 2015 and winter 2015/2016) in three clinics using a choice-based conjoint analysis (CA). Relevant therapy attributes and their levels were identified through literature search and expert interviews. Inclusion criteria were as follows: PR-inpatient with asthma and/or COPD, confirmed diagnosis, age over 18 years, capability to write and read German, written informed consent obtained. The CA analyses comprised a generalized linear mixed-effects model and a latent class mixed logit model. Results: A total of 542 persons participated in the survey. The most important attribute was sport and exercise therapy. Rehabilitation preferences hardly differed between asthma and COPD patients. Health-related quality of life (HRQoL) as well as time since diagnosis were found to have a significant influence on patients' rehabilitation preferences. Conclusions: Patients in pulmonary rehabilitation have preferences regarding specific program components. To increase the adherence to, and thus, the effectiveness of rehabilitation programs, these results must be considered when developing or optimizing PR-programs.
Keywords: 330; Patient preferences; Asthma; COPD; Chronic obstructive pulmonary disease; Choice-based conjointanalysis; Pulmonary rehabilitation; Latent class model; Mixed-effects model